A Analisis Kinerja Keuangan Bank BTPN Syariah Periode 2019-2021 - Ghina Azizah, Jihan; Umiyati; Obrian, Dea Diva; Zahiranita, Delia Putri (Jurnal Ilmiah Wahana Akuntansi, 2024)
This research analyzes the financial performance of Bank BTPN Syariah during the 2019-2023 period using the RGEC, Altman Z-Score and DEA methods. The results show that Bank BTPN Syariah has a capital adequacy level (CAR) that is consistently above regulatory standards, reflecting strong stability. An average technical efficiency level of 81% indicates good resource management, although there are variations in efficiency across years. Z-Score analysis shows an improving trend of stability in 2023, but still requires further strengthening. Bankruptcy predictions using the Altman Z-Score placed banks in the "healthy" category throughout the study period, reflecting resilience to financial risk. Digital transformation, asset optimization and focus on empowering the unbankable segment contribute to the sustainability of bank performance. This research confirms that Bank BTPN Syariah is able to maintain stability and efficiency, although there is still room for increasing competitiveness and risk management in the future.